Amelioration of the haloperidol-induced memory impairment and brain oxidative stress by cinnarizine - Abdel-Salam, Omar M.E; El-Mosallamy, Aliaa E.M.K.; El-Shamarka, Marwa El-Sayed; Salem, Neveen A.; Sleem, Amany A. (Technische Universität Dortmund, 2012)
Haloperidol is a classic antipsychotic drug known for its propensity to cause extrapyramidal symptoms and impaired memory, owing to blockade of striatal dopamine D2 receptors. Cinnarizine is a calcium channel blocker with D2 receptor blocking properties which is widely used in treatment of vertiginous disorders. The present study aimed to see whether cinnarizine would worsen the effect of haloperidol on memory function and on oxidative stress in mice brain. Cinnarizine (5, 10 or 20 mg/kg), haloperidol, or haloperidol combined with cinnarizine was administered daily via the subcutaneous route and mice were examined on weekly basis for their ability to locate a submerged plate in the water maze test. Mice were euthanized 30 days after starting drug injection. Malondialdehyde (MDA), reduced glutathione (GSH) and nitric oxide (nitrite/nitrate) were determined in brain. Haloperidol substantially impaired water maze performance. The mean time taken to find the escape platform (latency) was significantly delayed by haloperidol (2 mg/kg, i.p.) on weeks 1-8 of the test, compared with saline control group. In contrast, those treated with haloperidol and cinnarizine showed significantly shorter latencies, which indicated that learning had occurred immediately. Haloperidol resulted in increased MDA in cortex, striatum, cerebellum and midbrain. GSH decreased in cortex, striatum and cerebellum and nitric oxide increased in cortex. Meanwhile, treatment with cinnarizine (20 mg/kg) and haloperidol resulted in significant decrease in MDA cortex, striatum, cerebellum and midbrain and an increase in GSH in cortex and striatum, compared with haloperidol group. These data suggest that cinnarizine improves the haloperidol induced brain oxidative stress and impairment of learning and memory in the water maze test in mice.
EXCLI Journal ; Vol. 11, 2012
Keywords: brain; cinnarizine; haloperidol; oxidative stress; water maze; 610